Diagnosing the less common skin tumors : clinical appearance and dermoscopy correlation - Longo, Caterina, MD (Boca Raton, FL : CRC Press, 2019)
Caterina Longo, MD, PhDAssociate Professor, Dermatology and Venereology, at Universitaa degli Studi di Modena e Reggio Emilia (UNIMO); Azienda Unitaa Sanitaria Locale - IRCCS di Reggio Emilia, Centro Oncologico ad Alta Tecnologia Diagnostica, Modena, Italy; President of AIDNID; Executive Board Member of the International Dermoscopy Society Many texts deal with how to diagnose the straightforward melanomas of the skin, but there are many less common skin tumors that a clinician needs to be aware of because these are still likely to be encountered at some point in a clinical setting and many of them have serious implications. This highly illustrated text from an internationally acclaimed researcher provides a reliable guide to how to proceed with diagnosis of these more challenging entities. Contents: Tumors of the Epidermis: Nevoid basal cell carcinoma syndrome * Fibroepithelioma of Pinkus * Basosquamous carcinoma * Verrucous carcinoma * Sarcomatoid squamous cell carcinoma * Lentigines, Nevi, and Melanoma: Atypical Spitz nevus (tumor) * Halo Spitz nevus * Desmoplastic nevus * Pigmented epithelioid melanocytoma * Animal-type melanoma * Nevoid melanoma * Balloon cell melanoma * Desmoplastic melanoma * Special site melanoma (mucosal, acral) * Tumors of Cutaneous Appendages: Trichoadenoma * Trichoepithelioma and Brooke-Spiegler syndrome * Desmoplastic trichoepithelioma * Trichoblastoma * Tumors of the follicular infundibulum * Tricholemmoma and tricholemmal carcinoma and Cowden syndrome * Pilomatrixoma * Fibrofolliculoma/trichodiscoma and Birt--Hogg-Dubae syndrome * Sebaceous tumors *Syringocystadenoma papilliferum * Hidradenoma * Cylindroma and familial cylindromatosis and Brooke-Spiegler syndrome * Spiradenoma * Mammary and extramammary Paget's disease * Syringoma * Eccrine poroma and eccrine porocarcinoma * Mesenchymal Tumors: Dermatofibrosarcoma protuberans * Atypical fibroxanthoma * Malignant fibrous histiocytoma (pleomorphic undifferentiated sarcoma) * Other Uncommon Tumors: Merkel cell carcinoma * Kaposi's sarcoma * Angiosarcoma * Retiform hemangioendothelioma With contributions from: Alessandro Annetta * Giuseppe Argenziano * Elisa Benati * Caterina Bombonato * Stefania Borsari * Eugenia Veronica Di Brizzi * , Gerardo Ferrara * Giorgio La Viola * Mara Lombardi * Elvira Moscarella * Riccardo Pampena * Giovanni Paolino * Simonetta Piana
OCLC-licensed vendor bibliographic record.
Keywords: Skin -- Tumors -- Diagnosis; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / General; MEDICAL / Dermatology; MEDICAL / Family & General Practice